Kugaluk Site and the Nuvorugmiut : The Archaeology and History of a Nineteenth-Century Mackenzie Inuit Society - Morrison, David A. (Book collections on Project MUSE., 1988)
Description of the archaeological excavation and analysis of the Kugaluk site located near Eskimo Lakes east of Tuktoyaktuk, Northwest Territories. The area was inhabited by the Nuvorugmiut, one of the branches of the Mackenzie Inuit who seasonally exploited the caribou and whale and may have had a stratified social structure.